Implementation of a Standardized Transfusion Protocol for Cardiac Patients Treated With Venoarterial Extracorporeal Membrane Oxygenation Is Associated With Decreased Blood Component Utilization and May Improve Clinical Outcome. (April 2018) - Cahill, Christine M.; Blumberg, Neil; Schmidt, Amy E.; Knight, Peter A.; Melvin, Amber L.; Massey, Howard T.; Delehanty, Joseph M.; Zebrak, Seth B.; Refaai, Majed A.
Abstract : BACKGROUND: Extracorporeal membrane oxygenation supplies oxygenated blood to the body supporting the heart and lungs. Survival rates of 20% to 50% are reported among patients receiving ECMO for cardiac arrest, severe cardiogenic shock, or failure to wean from cardiopulmonary bypass following cardiac surgery. Bleeding is one of the most common complications in ECMO patients due to coagulopathy, systemic anticoagulation, and the presence of large bore cannulas at systemic pressure. Absence of a standardized transfusion protocol in this population leads to inconsistent transfusion practices. Here, we assess a newly developed dedicated transfusion protocol in this clinical setting. METHODS: Data were retrospectively reviewed for the first 30 consecutive cardiac ECMO patients prior and post implementation of the ECMO transfusion protocol. Diagnoses, laboratory results, blood component utilization, and outcomes were collected and analyzed. RESULTS: Comorbidities were similar between the 2 eras, as well as the pre-ECMO ejection fraction ( P = .568) and duration on ECMO ( P = .278). Transfusion utilization data revealed statistically significant decreases in almost all blood components and a savings in blood component acquisition costs of 51% ($175, 970). In addition, an almost 2-fold increase in survival rate was observed in the post-ECMO transfusion protocol era (63% vs 33%; relative risk = 1.82; 95% confidence interval, 1.07–3.10; P = .028). CONCLUSIONS: Our data indicate that implementation of a standardized transfusion protocol, using more restrictive transfusion indications in cardiac ECMO patients, was associated with reduced blood product utilization, decreased complications, and improved survival. This multidepartmental approach facilitates better communication and adherence to consensus clinical decision making between intensive care unit, surgery, and transfusion service and optimizes care of complicated and acutely ill patients.